Insulin Resistance: Any Role in the Changing Epidemiology of Thyroid Cancer? - Malaguarnera, Roberta; Vella, Veronica; Nicolosi, Maria Luisa; Belfiore, Antonino (Frontiers in Endocrinology, 2017)
In the last few decades, the incidence of thyroid cancer (TC), namely of its papillary hystotype (PTC), has shown a steady increase worldwide, which has been attributed at least in part to the increasing diagnosis of early stage tumors. However, some evidence suggests that environmental and lifestyle factors can also play a role. Among the potential risk factors involved in the changing epidemiology of TC, particular attention has been drawn to insulin resistance and related metabolic disorders, such as obesity, type 2 diabetes and metabolic syndrome, which have been also rapidly increasing worldwide due to widespread dietary and lifestyle changes. In accordance with this possibility, various epidemiological studies have indeed gathered substantial evidence that insulin resistance related metabolic disorders might be associated with an increased TC risk either through hyperinsulinemia or by affecting other TC risk factors including iodine deficiency, elevated thyroid stimulating hormone (TSH), estrogen-dependent signaling, chronic autoimmune thyroiditis, and others. This paper reviews and summarizes the current literature evaluating the relationship between metabolic disorders characterized by insulin resistance and the risk for TC as well as the possible underlying mechanisms. The potential implications of such association in TC prevention and therapy are discussed.